(untitled) (Journal of Academic Research, 2020)
The study aimed to measure whether Kida model could be used in predicting the financial failure of the Inma for Financial Investment Company, one year, two years and three years before it occurred during the period 2014-2017. The study also tested whether the value of the model increases as the period to be predicted for financial failure be closer. Having analyzing the data and using the deductive approach, the study reached a few conclusions, the most important of which was: the possibility of using Kida model in the forecasting process, and that the value of the model decreases, as the company continues, the closer the period to be predicted financial failure. In light of the findings, the study recommends a few recommendations, the most important of which is: inviting economic institutions operating in the Libyan environment to use Kida model in order to detect early whether the organization will face financial failure, or its activities will continue in the short run.